Size dependence of spin-wave modes in Ni80Fe20 nanodisks - P. Lupo; D. Kumar; A. O. Adeyeye (AIP Advances, 2015)
We investigate the radial and azimuthal spin-wave (SW) resonance modes in permalloy (Py: Ni80Fe20) disks at zero external magnetic field, as function of disk diameter and thickness, using broadband ferromagnetic resonance spectroscopy. We observed, from both experimental and micromagnetic simulation results that the number of SW absorption peaks increases with disk diameter. Numerically calculated SW mode profiles revealed a characteristic minimum size, which does not scale proportionately with the increasing disk diameter. We show that higher order modes could thus be avoided with an appropriate choice of the disk diameter (smaller than the minimum mode size). Moreover, based on the mode profiles, the existence of azimuthal SW modes with even number of crests or troughs can be ruled out. These results could be useful in enhancing our fundamental understanding as well as engineering of new magnonic devices.